(untitled) (Archive of Conferences, 2020)
English language is getting more and more globalized leading to the formation of its varieties in different countries across the world. In many countries English language is considered to be as a foreign or second language to learn for academic and personal goals. In Uzbekistan it is widely evident that many people learn English language as a foreign language in many educational settings. Many high educational institutions prepare English language teachers, and there are enough language courses that assist future teachers in developing their English language skills. Ergo, many students, who major in English language at high educational settings, are not fully aware of all English varieties and are not able to distinguish its types due to lack of practical part on the varieties of English